Economic implications of implementing the bureaucratic reform roadmap in the regional medium-term development plan: A strategic effort to enhance public service quality - Rahadian Auliansyah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The implementation of the bureaucratic reform roadmap in the Semarang City Medium-Term Development Plan is a strategic effort to improve the efficiency and effectiveness of public services and achieve sustainable development goals. Method: The implementation and understanding of the bureaucratic roadmap can be carried out through the use of qualitative methods. This selection method is in line with the need for descriptive analysis in the entire Semarang City government. Descriptive understanding is needed to examine the overall scope of the strategy. Findings: The bureaucratic reform roadmap includes a number of strategies, including the development of human resource bureaucracy, strengthening governance, improving the quality of public services, and implementing information technology. To face global and local challenges, the Semarang City Government prioritizes transparency, accountability, community participation, and innovation in every step of implementation. Strengthening governance is also an important step in implementing the roadmap. Conclusion: Although there are still several challenges to be faced, such as limited budget allocation and obstacles from several parties to change, the bureaucratic reform roadmap in the Semarang City RPJMD shows the government's seriousness in improving the quality of public services and achieving sustainable development in the future. Novelty/Originality of the Study: This study provides a novel assessment of the implementation of the bureaucratic reform roadmap, emphasizing strategies for human resource development, improving governance, and enhancing public services. The study highlights the role of transparency, accountability, and innovation in addressing challenges in bureaucratic transformation.